Antibiotic abuse: A cross-sectional study on knowledge, attitude, and behaviour among undergraduate students of western Nepal - Deo, Satish Kumar; Parajuli, Bijaya; Sapkota, Biswash; Dahal, Aashma (Journal of Kathmandu Medical College, 2023)
Background: Antibiotic abuse has drawn the attention of public health experts, stakeholders, and medical science due to the substantial economic loss that it causes to individuals and nation. Objectives: To assess the knowledge, attitude, and behaviour on antibiotic abuse among undergraduate level students of Pokhara, Nepal.Methods: This analytical cross-sectional study was conducted after ethical clearance in 361 undergraduate level students of Pokhara, Nepal from 2022 November to 2023 January. Convenience sampling technique was utilised for data collection. Data were analysed primarily by Chi-square test to find the associated factors using SPSS v.21.Results: A total of 361 respondents participated, and 61.77% were female. Most of the respondents (67.31%) were from health sciences, while 32.68% of the respondent was of non-health sciences. The mean age of the respondents was 20.97 ± 1.56 years. More than half of the respondents had inadequate knowledge and unfavourable attitude towards antibiotics while the prevalence of self-medication was found to be 72.6%.Conclusion: This study recommends for further large-scale research to understand the current state of antibiotic use and misuse among general population. Self-medication rate was high regardless of perceived knowledge and positive attitude. So, this study urges for the need of behavioural interventions that aims at raising awareness and establishing effective use of antibiotics.